PERANCANGAN INTERIOR SALON & SPA MARTHA TILAAR DI JAKARTA - Ambarwati, Novia; Nadaa, Zulfiska (Anggada : Jurnal Desain dan Seni, 2020)
The high awareness of Indonesian people on the importance of appearance makes many of woman and man do beauty treatments and body relaxation. Now the development of beauty salons and spas in Indonesia is becoming a competition. In the midst of increasing community activity that is dense and a high lifestyle makes many of the beauty service providers compete to be able to provide the best service. No exception is PT. Cantika Puspa Pesona who founded Martha Tilaar Salon Day Spa which provides a container for Indonesian people to be able to experience physical and relaxation beauty treatments and Martha Tilaar Salon Day Spa is also the best beauty service provider in Indonesia The interior design of Martha Tilaar Salon Day at the Pondok Indah uses the concept of "Modern Luxury with Javanese Culture", which is the use of modern style and Luxury interior impression by giving a touch of Javanese culture. The idea that appears in the interior design is based on the majority of the visitors who are of high social status, so it is expected to introduce and invite the people to continue and preserve Indonesian Culture through its application in the interior.